2016
DOI: 10.11002/kjfp.2016.23.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics and antioxidant activities ofmakgeolli prepared using rice nuruk containing bitter melon (Momordica charantia)

Abstract: Bitter melon powder (BMP) was used in the preparation of rice nuruk (RN) and makgeolli as one of raw materials. RN containing BMP (BMP-RN) was prepared by adding 0~2.0% (w/w) BMP into rice. Fermentative microbial, and antioxidant characteristics of makgeolli were determined during the fermentation process. pH during fermentation decreased from 4.52 (0% BMP-RN), 4.93 (0.5%), 4.80 (1.0%), and 4.88 (2.0%) on the initial fermentation day (day 0) to 4.15, 4.30, 4.57, and 4.59, respectively, corresponding to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…The ABTS radical scavenging capacity of QM was similar to that of Enteromorpha prolifera Makgeolli (90.60%) (Kim et al, 2020). Similar to this study, Cho et al (2016) reported that the ABTS radical scavenging capacity of Makgeolli prepared using rice Nuruk containing bitter melon ( Momordica charantia ) was 92.39%.…”
Section: Resultssupporting
confidence: 85%
“…The ABTS radical scavenging capacity of QM was similar to that of Enteromorpha prolifera Makgeolli (90.60%) (Kim et al, 2020). Similar to this study, Cho et al (2016) reported that the ABTS radical scavenging capacity of Makgeolli prepared using rice Nuruk containing bitter melon ( Momordica charantia ) was 92.39%.…”
Section: Resultssupporting
confidence: 85%
“…The carrot imparts β-carotene and other functional materials to Makgeolli with anti-cancer and anti-inflammatory properties. Cho et al (2016) suggested the preparation of rice Nuruk with bitter melon powder, remarkably improve the beneficial Bacteroidetes by dimishing pathogenic Firmicutes. Makgeolli derived from these Nuruk have higher content of soluble bioactive phenolic compounds and markedly increase the antioxidant characteristics.…”
Section: Flavor Varieties In Makgeolli and Health Benefitsmentioning
confidence: 99%